Analisis Pengaruh Temperatur Ambient Terhadap Kinerja Cooling Tower Unit 2 Berdasarkan Evaluasi Range dan Approach pada PLTGU PT Mitra Energi Batam - Firman Manahan Panjaitan; Putra, Irwanto Zarma (JURNAL INTEGRASI, 2025)
PLTGU PT. Mitra Energi Batam has observed that Cooling Tower Unit 2 tends to produce hot steam in larger quantities compared to Unit 1. The greater production of hot steam in Cooling Tower Unit 2 certainly cannot be separated from the influence of ambient temperature (surrounding air temperature). Where the temperature around the Cooling Tower Unit 2 environment affects the performance of the Cooling Tower. The cooler the environment, the better the cooling tower performance. This research aims to determine the extent of influence of ambient temperature on the performance of Cooling Tower Unit 2 in terms of Range and Approach calculations and to evaluate the difference between "Range" and "Approach" calculations in measuring the performance of Cooling Tower Unit 2. Data collection was carried out for 8 hours in 1 days out of 10 days of data collection in November 2023. The Cooling Tower performance calculation method used is Range and Approach Evaluation, where Range is a calculation of incoming water temperature with outgoing water temperature and Approach is a calculation of outgoing water temperature with Wet Bulb Temperature (ambient air temperature Cooling Tower). Based on the Range Value Evaluation, the calculation results were found to be in the range of 9.52°C – 9.97°C and 8,391°C – 10,331°C. If the Range Value is smaller then the Cooling Tower performance can be said to be good, for the Approach Value the calculation results are found to be 16,515°C – 18,205°C and 17,625°C – 21,892°C. If the Approach value is smaller, then the Cooling Tower performance can be said to be good because the outlet water temperature can approach the value of the wet bulb temperature. For the Efficiency Value, the calculation results obtained were at values of 34.98°C – 37.26°C and 28.44% - 35.68%.